In vitro interactions between bacteria, osteoblast-like cells and macrophages in the pathogenesis of biomaterial-associated infections. - Guruprakash Subbiahdoss; Isabel C Saldarriaga Fernández; Joana F da Silva Domingues; Roel Kuijer; Henny C van der Mei; Henk J Busscher (PLoS ONE, 2011)
Biomaterial-associated infections constitute a major clinical problem that is difficult to treat and often necessitates implant replacement. Pathogens can be introduced on an implant surface during surgery and compete with host cells attempting to integrate the implant. The fate of a biomaterial implant depends on the outcome of this race for the surface. Here we studied the competition between different bacterial strains and human U2OS osteoblast-like cells (ATCC HTB-94) for a poly(methylmethacrylate) surface in the absence or presence of macrophages in vitro using a peri-operative contamination model. Bacteria were seeded on the surface at a shear rate of 11 1/s prior to adhesion of U2OS cells and macrophages. Next, bacteria, U2OS cells and macrophages were allowed to grow simultaneously under low shear conditions (0.14 1/s). The outcome of the competition between bacteria and U2OS cells for the surface critically depended on bacterial virulence. In absence of macrophages, highly virulent Staphylococcus aureus or Pseudomonas aeruginosa stimulated U2OS cell death within 18 h of simultaneous growth on a surface. Moreover, these strains also caused cell death despite phagocytosis of adhering bacteria in presence of murine macrophages. Thus U2OS cells are bound to loose the race for a biomaterial surface against S. aureus or P. aeruginosa, even in presence of macrophages. In contrast, low-virulent Staphylococcus epidermidis did not cause U2OS cell death even after 48 h, regardless of the absence or presence of macrophages. Clinically, S. aureus and P. aeruginosa are known to yield acute and severe biomaterial-associated infections in contrast to S. epidermidis, mostly known to cause more low-grade infection. Thus it can be concluded that the model described possesses features concurring with clinical observations and therewith has potential for further studies on the simultaneous competition for an implant surface between tissue cells and pathogenic bacteria in presence of immune system components.